Component Analysis of Unsteady Hydrodynamic Force of Closed-Type Centrifugal Pump with Single Blades of Different Blade Outlet Angles - Yasuyuki Nishi; Junichiro Fukutomi (International Journal of Rotating Machinery)
Single-blade centrifugal impellers for sewage systems undergo both unsteady radial and axial thrusts. Therefore, it is extremely important for the improvement of pump reliability to quantitatively grasp these fluctuating hydrodynamic forces and determine the generation mechanism behind them. In this study, we conducted component analyses of radial and axial thrusts of closed, single-blade centrifugal pumps with different blade outlet angles by numerical analysis while considering leakage flow. The results revealed the effect of the blade outlet angle on the components of radial and axial thrusts. For increased flow rates, the time-averaged values of the pressure component were similar for all impellers, although its fluctuating components were higher for impellers with larger blade outlet angles. Moreover, the fluctuating inertia component of the impeller with a blade outlet angle of 8° decreased as the flow rate increased, whereas those with 16° and 24° angles increased. Therefore, the radial thrust on the hydraulic part was significantly higher for impellers with high blade outlet angles.